Manifestation of worldview in a metaphor - Bindlish P.K.; Nandram S.S. (My University, 2025)
Much of the current problems in organisations are emanating from the worldviews of the stakeholders involved in those organisations. The construct of worldview hails from the German word 'Weltanschauung'. It refers to the belief framework through which an individual or community (group, organisation, nation, civilisation) conceptualises reality and interprets the world and interacts with it. A closer look at the world around us reveals that most of our lives are being impacted by business organisations especially from the last few hundred years. Business entities are getting bigger and stronger day by day, especially with the power to take decisions which impact one and all. Therefore, it builds a case for analysis of organisational worldviews and their consequences on people, profit and the planet. One way of observing a worldview is through language. Applying it to organisations brings us to the concept of metaphor. This paper addresses how languages are manifestations of worldviews and what metaphor suits the elements of a new worldview representing the call for balance between people, profit and planet. It proposes the Banyan tree as a suitable metaphor for a natural worldview. Copyright © 2019 Inderscience Enterprises Ltd.